The Influence of Value-Co-Creation on Brand Equity: An Empirical Study in Saudi Arabia (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2020)
The current study aims to explore the influence of value co-creation on brand equity in a Saudi Arabia context. An attempt to illustrate the factors influencing brand equity from a consumer's perspectives as a result of changing customer's interests and lifestyle. Consumer's co-creation of value is powerful in understanding consumer behavior at its impact on brand equity. This paper has made an applied attempt in Saudi Arabia to study the mediation effect of positive e-WOM on value co-creation and brand equity, which adds to the knowledge line in the digital marketing discipline.